The Transformation Of Traditional Food as A Tourist Attraction to Visit Silalahi II Tourism Village, Dairi Regency - Mida Lishanata Simatupang (Politeknik Pariwisata Medan, 2022)
Silalahi II Tourism Village, Dairi Regency has great potential in food tourism (culinary tourism) because it has cultural wealth from a very heterogeneous community as residents of the Dairi Regency area, as well as assimilated remains the culture of the past community, each of which has its own special culinary. This study aims to identify culinary tourism in terms of: (1) the variety of menus offered (2) the process of transforming traditional foods and (3) tourists' perceptions of traditional foods. Data collection techniques include observation, questionnaires, interviews and documentation. The transformation process such as shape, texture, color, taste, processing and presentation method as well as sanitation hygiene. Presentation of results described qualitatively and quantitatively. Based on the results of the discussion that the menu offered has varied but the placement of the menu has not followed the order of international gastronomy and the service techniques used. The transformation process includes the processing of spices, equipment, texture, taste and presentation. Tourists' perceptions of traditional food offered are generally satisfied by 52% of 100 respondents. The suggestion from this research is the need for training, coaching and empowerment of restaurant managers or the general public related to factors of cleanliness, neatness and politeness of waiters to standardize taste and presentation.